Kinerja pemasaran yang dipengaruhi oleh orientasi pasar, inovasi produk dan bauran promosi - Dahmiri, Dahmiri; Kartika Wulan Bhayangkari, Sylvia (Jurnal Paradigma Ekonomika, 2022)
This study aims to perform a simultaneous and partial analysis of marketing performance influenced by market orientation, product innovation, and promotion mix variables in food and beverage Small & Medium Enterprises (SMEs), members of the Association of Food and Beverage Entrepreneurs (ASMAMI) of Jambi City. The study population was all ASMAMI members, amounting to 160 people, and at the same time used as a sample. This study uses survey techniques, with data collection using a closed questionnaire. The research method used is quantitative with analysis tools in the form of multiple linear regression. The research findings are that the marketing performance of food and beverage SMEs of the members of the City of Jambi ASMAMI is influenced by market orientation variables, product innovation, and promotion mix both simultaneously and partially. The more dominant variable in influencing marketing performance is the product innovation variable.